2020
DOI: 10.1371/journal.pone.0242802
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm in primary school-aged children: Prospective cohort study

Abstract: Introduction No prospective studies have examined the prevalence, antecedents or concurrent characteristics associated with self-harm in non-treatment-seeking primary school-aged children. Methods In this cohort study from Melbourne, Australia we assessed 1239 children annually from age 8–9 years (wave 1) to 11–12 years (wave 4) on a range of health, social, educational and family measures. Past-year self-harm was assessed at wave 4. We estimated the prevalence of self-harm and used multivariable logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…Our finding that problems with family members and peers are commonly cited problems in children who self-harm is in line with earlier reports from Australia [ 18 ] and the USA [ 6 ]. This adds to an extensive body of literature about the link between thwarted social ties and self-harm in children and adolescents [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that problems with family members and peers are commonly cited problems in children who self-harm is in line with earlier reports from Australia [ 18 ] and the USA [ 6 ]. This adds to an extensive body of literature about the link between thwarted social ties and self-harm in children and adolescents [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…The abrupt increase in girls self-harming at age 12 years was striking. It may well reflect the onset of puberty and its recognised association with increased risk of self-harm in girls [16,17] although a study involving more than 1000 under 13-year-old community-based non-treatment seeking children in Australia has shown that past year self-harm at age 11-12 years was more likely in children who were in mid-late puberty or late puberty relative to early puberty [18]. Other relevant factors might include starting secondary education, although one would perhaps expect similar effects in boys.…”
Section: Gender Ratiomentioning
confidence: 99%
“…We have captured presentations from 8 years of age, which is important as mental health concerns, particularly self-harm, are presenting from preadolescence. 29 30 The results are generalisable to other states and territories in Australia and countries with similar demographics, as the data were gathered from all public hospitals EDs in NSW in the EDDC registry. The larger EDs participate in the EDDC meaning a substantial proportion of the NSW population is covered; however, this varies over time and does not capture the full population of NSW with lower participation from hospitals in rural and remote regions.…”
Section: Discussionmentioning
confidence: 83%
“…This is the first Australian study to examine mental health ED re-presentations among young people. We have captured presentations from 8 years of age, which is important as mental health concerns, particularly self-harm, are presenting from preadolescence 29 30. The results are generalisable to other states and territories in Australia and countries with similar demographics, as the data were gathered from all public hospitals EDs in NSW in the EDDC registry.…”
Section: Discussionmentioning
confidence: 99%
“…Das selbstverletzende Verhalten beginnt bei einigen Betroffenen bereits früh: In einer großen australischen Studie gaben bereits 3 % der 11–12-Jährigen an, sich in den letzten 12 Monaten selbst verletzt zu haben 21 . In einer anderen Übersichtsarbeit gaben bis zu 6 % der Kinder unter 12 Jahren ein NSSV an 22 .…”
Section: Introductionunclassified